Odpowiedź:
A)
4x + 4y = 8
2x+2y =4 / * (-2)
4x + 4y = 8
-4x - 4y =-8
-4x +4x - 4y + 4x = 8 - 8
0 = 0
B)
-3x +2y =-1 / * 2
2x-3y=1 / * 3
-6x +4y =-2
6x-9y=3
-6x + 6x -9y + 4y = 3 - 2
-5y = 1 / : (-5)
y = -1/5
Obliczenia dla x :
-3x +2 * (-1/5) = -1
2x-3 * (-1/5)=1
-3x + 2/1 * (-1/5) = -1
2x - 3/1 * (-1/5)=1
-3x + (-2/5) = -1
2x - (-3/5)=1
-3x -2/5 = -1 / + 2/5
2x + 3/5=1 / -3/5
-3x = -1 + 2/5
2x =1 -3/5
-3x = -1/1 + 2/5
2x =1/1 -3/5
-3x = -1/5 + 2/5
2x =1/5 -3/5
-3x = 1/5
2x = -2/5
-3x + 2x = 1/5 -2/5
-1x = -1/5 / : (-1)
x = 1/5
Odp. W b) x =1/5 i y = -1/5